Increased concentration of tumour necrosis factor alpha in the plasma of glaucoma patients - Trenkić Marija; Jevtović-Stoimenov Tatjana; Bašić Jelena; Vasilijević Jelena; Ristić Dragana; Trenkić Milan; Veselinović Aleksandar; Cvetanović Marija (Vojnosanitetski Pregled)
Background/Aim. Changes in the concentration of various mediators of inflammation in blood, aqueous humor, or eye tissues support the role of inflammation in the pathogenesis of open-angle glaucoma (OAG). Inflammatory biomarkers have a great potential for application in clinical practice. The aim of the study was to determine concentrations of tumor necrosis factor (TNF)-α in the plasma of patients with OAG and subjects without glaucoma and examine the correlation between the TNF-α concentration in plasma in glaucoma patients and specific clinical parameters. Methods. The study included 87 participants (87 eyes) divided into three groups: 35 subjects (35 eyes) with primary OAG (POAG) with elevated intraocular pressure (IOP) – hypertension glaucoma (HTG) (POAG-HTG), 23 subjects (23 eyes) with pseudoexfoliative OAG (XFG), and 29 subjects in the control group (healthy subjects) matched with the patient groups in terms of age and gender. We performed a complete clinical examination, including standard automated perimetry and determination of changes in the participant’s repeated visual field, optical coherence tomography and determination of peripapillary retinal nerve fiber layer (RNFL) thickness. The concentration of TNF-α in participants’ plasma was measured using commercial enzyme-linked immunosorbent assay – ELISA. Results. The concentrations of TNF-α in the plasma of glaucoma patients (POAG-HTG 2.04 ± 1.98 pg/mL and XFG OAG 2.05 ± 1.48 pg/mL) were significantly higher than in healthy subjects (1.43 ± 2.00 pg/mL, p < 0.05). In none of the groups of subjects suffering from glaucoma was there a statistically significant correlation of TNF-α concentration in the plasma with any of the clinical parameters, including IOP, cup/disk ratio, mean deviation, average RNFL, and RNFL in the superior and inferior quadrant. Conclusion. The concentration of the pro-inflammatory cytokine TNF-α in the plasma is significantly higher in glaucoma patients compared to non-glaucomatous subjects, and it confirms the role of inflammation in the pathogenesis of glaucoma as one of the non-inflammatory ocular diseases. The concentrations of TNF-α in the plasma of glaucoma patients did not correlate with any of the examined clinical parameters; hence, it cannot be considered a measure of progression and damage in glaucoma.